Optimizing Vacant Land in Establishing Nutrient Gardens in Gebang Hamlet, Blagung Village, Simo District, Boyolali Regency - Muhammad Mustaqim; Dewi Nur Azizah; Mauly Khalwa Azzahra; Muhammad Faiz Faza Arhama; Azhar Maulana (Prospect: Jurnal Pemberdayaan Masyarakat, 2024)
In the midst of global challenges related to food security and rapid population growth, the Nutrition Garden program in Gebang Hamlet, Blagung Village, Simo District, Boyolali Regency is an important initiative in improving the welfare and food security of rural communities. Gebang Hamlet has potential empty land that has not been utilized optimally. Mapping assets and potential, such as natural resources, human resources, social resources, cultural resources and economic resources, is the first step to identify potential for developing nutritional gardens. Through this program, people can meet their needs for fruit and vegetables, increase awareness of balanced nutrition, and contribute to preventing stunting. The use of the ABCD (Asset-Based Community Development) methodology makes it possible to explore community potential and assets more effectively. The implementation stages include clearing the land, selecting seeds and seeds, planting, watering and harvesting, with active participation from the Gebang Hamlet community. The results of the Nutrition Garden program will be measured through plant growth, community participation, and harvest yields. This program not only aims to improve food security, but also to provide additional income opportunities for local communities and encourage sustainable agricultural practices. The Dusun Gebang Nutrition Garden Program is expected to provide sustainable benefits for the community, improve welfare, and provide inspiration for other regions in efforts to develop community-based food security.